A bibliometric analysis of 30 years of research on transarterial radioembolization (TARE) for hepatocellular carcinoma - Hu, Tongyao; Xu, Qifan; Jia, Guorong; Wang, Tao; Zuo, Changjing (Frontiers in Pharmacology, 2025)
IntroductionPatients with advanced hepatocellular carcinoma (HCC) have very limited treatment options, among which transarterial radioembolization (TARE) receives increasing attention, relying on its promising efficacy and fewer side effect. However, a bibliometric analysis of TARE for HCC is still lacking. This study employed bibliometric methods to analyze the related articles over the past three decades, and aimed to identify trends in clinical research comparing TARE to other treatments.MethodsArticles related with TARE for HCC were obtained from the Web of Science (WoS). After screening, the R package Bibliometrix was employed to explore the primary bibliometric characteristics. The number of publications was analyzed and mathematically fitted to a curve using Microsoft Excel 2021 and SPSS 25, and then was plotted in the graph using GraphPad Prism 8.0. VOSviewer, SCImago Graphica, and Pajek were utilized for the analysis of researchers’ co-authorship, co-occurrence, and visualization. Keywords citation burst was detected by CiteSpace software.ResultsA total of 1,110 articles from 1993 to 2023 were included in our final analysis, among which the United States not only ranked the first in term of the number of published articles, also was at the forefront in other important indicators, including the total number of article citations and the average citation frequency. Riad Salem from Northwestern University, also being the organization with the greatest number of research papers, was the most active author and has published 96 papers. The keywords were classified into three clusters: 90Y microspheres for TARE, Basic research on TARE, and Clinical trial of TARE for HCC. Furthermore, we identified the most frequently cited keywords with strong citation bursts since 2020 were “multicenter,” “overall survival” and “PET/CT.”ConclusionOur study employed a bibliometric approach to achieve the visualization research on TARE for HCC, and further revealed the trends and frontiers of TARE research, providing valuable information for researchers to identify the critical and persistent challenges and select potential partners in related area. Based on our analysis, future research focus include the clinical comparative studies on the effect of TARE and TACE combined with immunotherapies or targeted therapy, dosimetry, and personalized TARE therapy for HCC.